2015
DOI: 10.2224/sbp.2015.43.10.1593
|View full text |Cite
|
Sign up to set email alerts
|

Stand-Alone Sale of a Free Gift: Is it Effective to Accentuate Promotion Value?

Abstract: Offering a free gift when a purchase is made is one of the most pervasive marketing practices. We investigated whether making the product offered as a free gift also available for sale by itself (i.e., a stand-alone sale of the gift product) accentuated the customer's perception of the value of the promotion. Previous research on value anchoring and adjustment predicted that a stand-alone sale of a gift would increase the promotion value, whereas the opposite was predicted in the scarcity perception literatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Therefore, comparing results from Nigeria and other populations in developing counties should be done with caution, as participants in the current study, done in Central America, received free amplification. Research by Kim and Koo [20] indicated that offering a product as a free gift will influence the consumer's value of that gift. It is possible that the free amplification given to the patients in the current study may have caused them to report greater satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, comparing results from Nigeria and other populations in developing counties should be done with caution, as participants in the current study, done in Central America, received free amplification. Research by Kim and Koo [20] indicated that offering a product as a free gift will influence the consumer's value of that gift. It is possible that the free amplification given to the patients in the current study may have caused them to report greater satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, consumers may infer the fair price of a product from a sales promotion by thinking about the cost structure and the normal margin (Raghubir, 2006). Consumers may discount the stand-alone value of the gift product as well, because being given away for free implies its low cost (Kim and Koo, 2015;Raghubir, 2004). Similarly, consumers may make negative inferences about the promoted product in response to a free gift promotion because of the appearance that the incentive gift is needed to generate sales.…”
Section: Free Gift Promotions and Persuasion Knowledgementioning
confidence: 99%
“…supplementary product). Studies have shown that providing free gifts in a promotion has been one of the most pervasive marketing strategies (Kim and Koo, 2015; Sexton, 1987).…”
Section: Introductionmentioning
confidence: 99%